Molecular identification of the main raptor bird species from the Arequipa-Lima region, Peru, using sanger sequencing - Wilmer Julio Paredes Fernandez; Maria Elena Suaña Quispe; Adolfo Roman Ramos Paredes; Erick Andy Huarilloclla Cordova; Thyfanny Brigitte Cuellar Ramos; Holger Mayta Malpartida (Acta scientiarum. Biological sciences, 2025)
A total of 14 feather samples were collected from the following birds of prey: Buteo polyosoma, Geranoaetus melanoleucus, Bubo magellanicus, Athene cunicularia, Falco sparverius, Vultur gryphus, Spizaetus ornatus, Falco rufigularis, Morphnus guianensis, Oroaetus isidori, Spizaetus melanoleucus, Spizaetus tyrannus, Harpyhaliaetus solitarius, and Accipiter bicolor. The taxonomic identity of 12 birds of prey species from two regions was inferred, with similarity percentages ranging from 99-100% compared to the database sequences. While the amplification of D-Loop/12S was unsuccessful due to the specific primers for Vultur gryphus, the COI and NAD2 regions showed high efficacy in the molecular identification of the analyzed samples. The analysis of the COI and NAD2 sequences revealed a marked intraspecific genetic divergence, with divergence percentages of up to 6-8% in some Neotropical birds of prey from Arequipa compared to the reference sequences. This finding suggests more complex patterns of variability and differences in regional sequence homology in these species than in North American birds. DNA barcodes based on mitochondrial sequences, particularly COI and NAD2, have proven to be accurate and non-invasive tools for the taxonomic identification of these birds of prey using feather samples as a source of genetic material.